Fuzzy-Wuzz, a little brown bear of the Sierras - Chaffee, Allen, 1884-1985; DaRu, Peter, 1883-1964 (Salt Lake City, UT : Project Gutenberg, 2023)
"Fuzzy-Wuzz, a Little Brown Bear of the Sierras" by Allen Chaffee is a children's novel written in the early 20th century. The story follows the adventures of Fuzzy-Wuzz, a small bear cub, as he navigates life in the high Sierras alongside a cast of animal friends, including a fawn, a burro, and various other woodland creatures. The book combines elements of natural science and storytelling, providing young readers with both entertainment and education about the diverse wildlife in the Sierra Nevada mountains. At the start of the tale, readers are introduced to Fuzzy-Wuzz as a baby bear who is rescued by a Forest Ranger after almost drowning. He is brought to a cabin where he becomes part of the Ranger's family, sharing space with children and other animals like a fawn named Dapple. The opening chapters depict Fuzzy-Wuzz's early experiences, including his exploration of the forest, learning to swim, and adapting to life outside his mother's care. The narrative sets the stage for the adventures that await him, including encounters with various animals and challenges in the wild, establishing a lively and engaging atmosphere for the reader. (This is an automatically generated summary.)
Release date is 2023-02-01
Charlene Taylor, Krista Zaleski and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Animals -- Juvenile fiction